CORRELATION OF AA INDEX WITH DEGREE OF LIVER FIBROSIS IN CHRONIC HEPATITIS B PATIENTS - Rika Andriany; Ibrahim Abdul Samad; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
A liver biopsy is the gold standard for diagnosing and staging liver fibrosis in chronic hepatitis B patient but with many disadvantages so it is difficult to use as a routine examination. Research on index based on serum marker is helpful in predicting liver fibrosis. We conducted a study of the alpha-fetoprotein (AFP) and partial activated thromboplastin time (APTT) index or AA index in relation to the degree of liver fibrosis in chronic hepatitis B patients. This study was a retrospective cross-sectional study in dr.Wahidin Sudirohusodo Hospital Makassar by taking the data from medical records of chronic hepatitis B patients from January 2015 to December 2016. Samples were chronic hepatitis B patients who were tested for AFP, APTT and Fibroscan. The result showed the total of 79 chronic hepatitis B patients, 23 with severe fibrosis, 9 with moderate fibrosis, 26 with mild fibrosis, and 21 with no fibrosis. Spearman correlation test showed a significant correlation between the AA index and the degree of fibrosis (p <0.001) and showed a positive correlation between both of them with a very strong correlation (r = 0.830). Oneway Anova test showed a significant difference between the AA index and the degree of fibrosis (p<0.001). The results of this study indicate that the AA index can be used as a predictor of fibrosis in chronic hepatitis B patients. It is suggested to do another study with larger sample based on the degree of fibrosis.